Do executive compensation and government ownership effected performance banking listed in Asean? - Rut Nova Gita Sihombing; Doddy Setiawan (University of Merdeka Malang, 2022)
This study identifies and analyzes the relationship between executive compensation and government ownership effected performance banking listed in Asean. The research sample is 96 Asean listed companies. This study examines the static between the framework, which controls for the specific effects of each of the factors being tested. This study finds that executive compensation has effect positively on ROE and Tobin’s Q. This finding indicates that investors perceive this as advantageous conditions. This indicates that executive compensation effect how board of executive improve bank performance. Another result shows that government ownership has a positive effect on bank performance.